Study on the Quality of Compressed Baker’s Yeast in Hasahissa Factory - H.A, Mudawi,; .Hb, Mohammed , I.E; A.H, El Tinay, (Gezira Journal of Engineering and Applied Sciences, 2018)
The main objective of  this study was to determine the quality of compressed baker's yeast at Hassahissa Yeast Factory in Sudan. The raw materials used in the production of the compressed baker's yeast were analyzed (molasses, urea, air, water and original strain). Chemical, physical and microbiological analysis were carried out. Chemical and physical analysis for treated molasses showed a decrease in total sugars, total soluble solids, specific gravity and pH value com-pared with the raw molasses. But during processing there was a decrease in pH and Brix values when applying batch process system, during applying continuous process the pH and Brix values were increased with increasing time. The concentration of cream (GPL) and yeast cell concentration (YCC)  increased during fermentation to specific time for batch and continuous process systems. Alcohol content was higher in the starter culture compared with the commercial batch. The chemical composition of the final products showed a high moisture content of 70.5%, protein 14.3%, ash 1.7%, fat 1.2% and carbohydrate 12.2%. The activity of yeast and CO 2 production were good. The time taken to leaven dough was 75 minutes and the baking test gave reasonable specific volume. Microbiological tests showed no contamination for original strain, but high contamination of air in the surroundings of the plant and factory chambers except culture room. Contamination in treated molasses and water was nil, but urea was contaminated. Also microbial contamination was rather low in starter culture than in the commercial batch. The final product showed a limited degree of contamination. The study recommended the improvement of the hygienic guards for both plant and workers and to use ultra violet sterilization techniques. Also, it is strongly recommended to manufacture dry yeast instead of compressed yeast to overcome the bad weather conditions in the Sudan.